2007
DOI: 10.1007/s00018-007-7389-z
|View full text |Cite
|
Sign up to set email alerts
|

Common Molecular Mechanisms of Mammary Gland Development and Breast Cancer

Abstract: Evidence is accumulating that breast cancer is not one disease but many separate diseases. DNA microarray-based gene expression profiling has demonstrated subtypes with distinct phenotypic features and clinical responses. Prominent among the new subtypes is 'basal-like' breast cancer, one of the 'intrinsic' subtypes defined by negativity for the estrogen, progesterone, and HER2/neu receptors and positivity for cytokeratins-5/6. Focusing on basal-like breast cancer, we discuss how molecular technologies provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Early breast cancer has a highly variable prognosis and the benefit of existing therapies is often unpredictable. Several morphological parameters, including tumor size, histological grade, vascular invasion and lymph node metastasis, are useful in this regard, but insufficient (8). This has lead to the study of tumor molecular characteristics and currently ER, PR and HER2 are recognized as prognostic and predictive factors (10,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early breast cancer has a highly variable prognosis and the benefit of existing therapies is often unpredictable. Several morphological parameters, including tumor size, histological grade, vascular invasion and lymph node metastasis, are useful in this regard, but insufficient (8). This has lead to the study of tumor molecular characteristics and currently ER, PR and HER2 are recognized as prognostic and predictive factors (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…The reaction to HER2 was scored as follows: 0 (negative), absent or present in <10% of tumor cells; 1+ (negative), membranous, weak and discontinuous in >10% of tumor cells; 2+ (questionable), membranous, low/moderate and continuous in >10% of tumor cells or membranous, intense and continuous in ≤30% of tumor cells; and 3+ (positive), membranous, intense and continuous in >30% of tumor cells. Cases were stratified as luminal breast carcinoma (ER + and/or PR + / ± HER2 + ) and non-luminal breast carcinoma (represented by all ER- and PR-negative cases) (5,7,8,24). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This should not come as a surprise, given that BRCA1 has been shown to play a pivotal role in the regulation of ER expression and that RNA interference-mediated silencing of BRCA1 in breast cancer cell lines leads to a marked reduction in expression of endogenous levels of ER (Hosey et al, 2007) and in increased expression of markers usually found in basal/myoepithelial cells (e.g. cytokeratins 5 and 17, and P-cadherin) (Gorski et al, 2009;Mullan, 2006).…”
Section: Genotypicephenotypic Correlationsmentioning
confidence: 99%
“…The developments of tumour subtyping and the availability of a broader range of treatments [ 4 ] are likely to lead to changes in how patients with breast cancer are managed clinically, as summarised in Fig. 1.…”
Section: Effect On Patient Care and Opportunities For Petmentioning
confidence: 99%